ANALISIS TINGKAT SWASEMBADA WILAYAH DI KABUPATEN SEMARANG - Eko Wibowo, Muhammad Nasrun; Banuwati, Eva; Arifien, Moch. (Geo-Image, 2016)
The located of this research in Semarang District of Central Java. It have three purpose, there are (a) to now a level of food self-sufficiency, (b) to make strategy for food self-sufficient that is count of optimum population. The method of research is quantitative describe with focused relation of variabels. The population is all of the land-farm and the sample is the land-rice. To analysis of the research used an analysis of point of field-rice carrying capacity, region self-sufficiency level and optimum population amount.Based on result of this research that is started from March – April 2016. The result of selfsufficienct level in Semarang district is 0,2. Its means population of citizen very big from optimum population amount. This condition will cause category Semarang District in level 1st (not yet self-sufficient). It is caused by pressure of population is very big, the farmer is very few just 10% or 97.531 people and a part of land-rice was conversion to industry central, dwelling, road and etc.